2008
DOI: 10.1007/s11605-007-0422-6
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Markers of Resectability in Patients Undergoing Exploration of Potentially Resectable Pancreatic Adenocarcinoma

Abstract: Despite extensive preoperative staging, a significant number of pancreatic cancers are unresectable at surgical exploration. Patients undergoing pancreatic exploration with a view to resection were studied and comparisons are then made between those undergoing resection and a bypass procedure to identify surrogate markers of unresectability. One hundred thirteen consecutive patients underwent pancreatic exploration for head-of-pancreas (HOP) adenocarcinoma with curative intent. Fifty-five underwent pancreatico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…The hazard ratio (HR) and 95 % confidence intervals (CI) were calculated for all estimates. The optimal cut-off values for NLR and PLR were determined using receiver operating characteristic (ROC) curve and the corresponding area under the ROC (AUROC) curve, and by referring to some previously published reports [10][11][12][13][14][15][16]. All statistical analyses were performed with the JMP 11.0 for Macintosh software program (SAS Institute Inc., Cary, North Carolina).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hazard ratio (HR) and 95 % confidence intervals (CI) were calculated for all estimates. The optimal cut-off values for NLR and PLR were determined using receiver operating characteristic (ROC) curve and the corresponding area under the ROC (AUROC) curve, and by referring to some previously published reports [10][11][12][13][14][15][16]. All statistical analyses were performed with the JMP 11.0 for Macintosh software program (SAS Institute Inc., Cary, North Carolina).…”
Section: Discussionmentioning
confidence: 99%
“…Although these prognostic factors have been explored in PDAC patients in some small cohort studies, the results still remain controversial because PDAC patients with diverse clinical stages were included in the cohorts [10][11][12][13][14][15][16][17]. The systemic inflammatory response has never been validated as a predictive risk factor in cohort that is restricted to advanced BR-PDAC patients.…”
Section: Introductionmentioning
confidence: 99%
“…12 Moreover, some investigators have found that elevated preoperative serum CA 19-9 levels are significantly associated with tumor unresectability, although the cut-off levels reported range from 100 to 350 IU/ml. [8][9][10][11][12][13][14][15][16][17] Based on these data, some speculate that preoperative staging of a potentially resectable PA should routinely include serum CA 19-9 levels after biliary decompression. In the case where careful preoperative staging indicates a radiographically resectable PA without evidence of distant metastasis but the serum CA 19-9 levels are highly elevated, the staging might be better clarified by the use of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Several reports have shown that a serum CA19-9 level above 200 or 300 IU/ml correlates with poor outcome and conclude that such patients will likely not benefit from surgery. [8][9][10][11][12][13][14][15][16][17] A minority of patients with resectable PA have high levels (>400 IU/ml) of serum CA19-9. Even when patients with high serum CA 19-9 are determined to be radiographically resectable, they will often have metastasis discovered at the time of laparoscopy or laparotomy.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] An elevated NLR has been found to be an indicator of poor prognosis in patients with CRC [14]. On the other hand, PLR role as prognostic indicator was found to be inconsistent as it was associated with decreased survival in some studies [15,16], whereas others did not demonstrate the relationship between prognosis and PLR [17,18].…”
mentioning
confidence: 99%